(untitled) (Productivity, 2020)
This study aims to determine whether Brand Image affects the Buying Decision at J.CO Donuts & Coffee Mega Mall Manado. This research is a type of quantitative research with a consumer population of J.CO & Coffee Mega Mall Manado. The sample size uses the opinion expressed by Roscoe, in the Research Method for book that the proper sample size in the study is between 30 and 500 is sufficient to be used in a study. Therefore, the sample in this study was 100 respondents. The data analysis technique used simple linear regression analysis. In the case of a simple regression test, the results show that partially there is an influence between Brand Image and Buying Decision. Validity and Reliability Test. The results of this study indicate the relationship between the influence of the Brand Image variable on the Purchase Decision by 70.2%, indicating that the results of this study have a positive and significant effect on the Purchase Decision of J.CO Donuts & Coffee Mega Mall Manado products partially.